FACTORS OF ESCALATION OF ETHNOPOLITICAL TENSION IN THE MODERN DAGESTAN SOCIETY - Sahbanova, M M (History, Archeology and Ethnography of the Caucasus, 2017)
The article deals with the factors ensuring interethnic stability in the modern Dagestan society, the assessment of the interethnic tension potential as the characteristics of (stable/conflict) interrelations among peoples, the ground for the formation of disintegrating processes, the causes of interethnic confrontation and exacerbation of interethnic relations, the base of the development ofattitude towards interethnic tolerance and intolerance, “cultural detachment”of the Dagestan peoples. The problem of harmonization of interethnic relations is one of the most important at the present stage of the development of the Russian society, and it is especially relevant in administrative territories characterized by diversity of ethno-social structure. Against the background of socio-economic stabilization of the noughties, the state-civil (Russian) and republican (Dagestan-wide) identities, gradually gaining weight, have significantly strengthened their positions in the structure of social identity. Moreover, republican identity now prevails over ethnic one,it allows to conclude that the importance of interethnic harmony in the Dagestan society is growing. Basing on the results of the sociological research, the author considers the reasons for exacerbation of interethnic relations, including territorial disputes, peculiarities of land reform, low level of socio-economic development of the republic, competition for land and workplaces, low culture of interethnic communication, migration of people from mountainous regions to flat land, employment issue, side effect of education and loss of principles of international education. Despite the existence of a latent form of interethnic confrontation and “social detachment”, in the mass consciousness of the respondents there is a positive perception of the Dagestan peoples, an orientation toward maintaining close interethnic communication in almost all spheres of social contact, except for family and marriage sphere.